THE INFLUENCE OF AKAD BA'I BITSAMAN AJIL ON VEHICLES TO INCREASING INCOME BMT AL-ISTIQOMAH CIAMIS - Sumadi Sumadi; Ahmad Rojul Ishak; Siti Rif’ah Nuralawiyah Esa (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2018)
Ba'i Bitsaman Ajil (BBA) financing is widely practiced by Islamic financial institutions including the BMT Al-Istiqomah. However, in the application of the Ba'i Bitsaman Ajil (BBA) contract at BMT Al-Istiqomah, it is different from other financial institutions. As in BMT AM-MU Pasuruan this financing is used to finance micro businesses and also at BMT Hudatama Semarang is used to finance home renovations. While at BMT Al-Istiqomah, the Ba'i Bitsaman Ajil contract was practiced to meet the needs of the community in financing vehicles in the form of motorbikes or cars. BMT Al-Istiqomah can contribute to helping people to have transportation vehicles. Therefore, the authors are interested in conducting research on the Influence of the Ba'i Bitsaman Agreement on the Vehicle Against Increasing Income of BMT Al-Istiqomah Ciamis. The research method used is descriptive-qualitative and quantitative methods (mixed method). While the data collection techniques used are observation, interviews, and documentation. To test the validity of the data, this research uses triangulation method. After analyzing the data, the authors draw the following conclusions: 1) the procedure for financing the Ba'i Bitsaman Ajil agreement that must be fulfilled by each prospective customer begins with the submission of the application until the approval of the realization of financing and using the principle of 5C financing (caracter, capital, condition) analysis. , capacity, and coreteral); 2) How to determine the Margin in the Ba'i Bitsaman Ajil agreement on vehicle financing at BMT Al-Istiqomah has fulfilled the requirements in calculating the sale and purchase by installments or installments as well as determining the margin of the principal price based on the agreement of both parties. (BMT and customers); 3) After data analysis which includes testing the hypothesis, the average income figure in BMT Al-Istiqomah Ciamis in the June-May 2016-2017 period is highest at the Ba'i Bitsaman Ajil agreement with an average number of 10,827,917 while from the other contract is the Murabahah contract 10,236,667, pawn contract 3,259,917, Rahn agreement 2,371,500. Musyarakah agreement 1,660,750, Hasan Qordu agreement 1,157,833. then it can be concluded that the contract of Ba'i Bitsaman Ajil greatly influences the increase in income of BMT Al-Istiqimah Ciamis compared to other contract products found on the BMT.